2009
DOI: 10.1097/nrl.0b013e3181901ad3
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Antiepileptic Drug Initiation and Withdrawal

Abstract: Drug initiation after a first seizure decreases early seizure recurrence, but does not affect the long-term prognosis of developing epilepsy. Medication withdrawal after a period of seizure remission increases the risk of relapse, but the benefits of successful AED discontinuation may be substantial. In the end, the decision of whether to initiate treatment after a single seizure and whether to withdraw AED therapy in patients enjoying a prolonged period of seizure freedom should be made on an individual case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 54 publications
0
21
1
2
Order By: Relevance
“…When AEDs were used throughout pregnancy, the most prevalent diagnoses were epilepsy and psychiatric disorders, which may be based on mounting evidence that, for many patients with epilepsy or psychiatric diagnoses such as bipolar disorder, the risk of maternal-fetal harm may be increased if effective pharmacotherapy is discontinued during pregnancy. 34-36 …”
Section: Discussionmentioning
confidence: 99%
“…When AEDs were used throughout pregnancy, the most prevalent diagnoses were epilepsy and psychiatric disorders, which may be based on mounting evidence that, for many patients with epilepsy or psychiatric diagnoses such as bipolar disorder, the risk of maternal-fetal harm may be increased if effective pharmacotherapy is discontinued during pregnancy. 34-36 …”
Section: Discussionmentioning
confidence: 99%
“…While some studies show that within the NCS/NCSE group, subjects with generalized ictal discharges had a worse prognosis compared to subjects with unilateral ictal discharges [34], others did not find any prognostic correlation with abnormal or epileptiform EEG [31]. In the context of AED withdrawal, a number of studies have identified factors associated with increased risk of relapse including multiple seizure types, focal epileptiform abnormalities on EEG, and worsening EEG patterns after AED discontinuation [29,[35][36][37]. While we did not analyze outcomes based on NCS/NCSE subtypes, we did find that the primary background EEG abnormality was similar to previously published studies and did not differ between the wean and non-wean groups.…”
Section: Discussionmentioning
confidence: 99%
“…Although this review focuses on the decision to withdraw an AED after a seizure-free interval, it is important to acknowledge a number of studies and reviews that have addressed the question of starting therapy [1,2,3,4,5,6,7,8,9]. After two unprovoked seizures, the risk of recurrence is relatively high [2], a diagnosis of epilepsy is made, and the accepted practice is to initiate an AED.…”
Section: Introductionmentioning
confidence: 99%
“…Some special factors may further increase the risk of recurrence, however, and this information should be presented to patients who are considering drug withdrawal. Several reviews of AED withdrawal have identified a number of factors associated with increased risk: an abnormal neurologic examination, IQ less than 70, longer duration of epilepsy, higher number of seizures, multiple seizure types, focal epileptiform abnormalities on EEG, and worsening EEG patterns after AED discontinuation [9,19]. Multiple studies have shown that longer duration of disease and earlier age of onset prior to the period of seizure freedom increase recurrence risk [13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%